PENGARUH MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA PT XXX - Sari, May; Sayekti, Wuryaningsih Dwi; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to determine the motivation, discipline, and the employees’ performance in PT XXX, the effect of work motivation on the employees’ discipline in PT XXX, and the motivation on the employees’ performance both directly and indirectly through discipline in PT XXX. The data collection was conducted in March 2017. The method used wasa case study because this study involved all members of the population from the study area. The available number of respondents in this study were 38 people. The first purpose was analyzed descriptively. The second and third purposes were analyzed using path analysis. The employees’ work motivation in PT XXX was included in the medium category (good enough). The discipline of the employees was inthe good category for each dimension of three, namely working time, carrying out the work, and obeyingrules. The employees’ performance in PT XXX was included in a good enough category. In this study motivation did not affect the employees’ discipline in PT XXX. Discipline had the biggest direct influence on the performance by 65.90 percent, compared with motivation by 36.50 percent, the indirect effect value of motivation on performance is 11.30 percent. Key words : dicipline, motivation, path analysis, performance employee